Southwest Research-Extension Center, Field Day 1998 (Kansas Agricultural Experiment Station Research Reports, 1998)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 1998; SRP814; crops; tillage; irrigation; insect control; weed science